The Perception Of Pamong Teacher Towards Students Practice Of Educational Field Private Vocational School Of Fpp Unp In Core Learning Activities at SMK Negeri 9 Padang - Febriani, Lia; Yelfi, Reno; Syarif, Wirnelis; Siregar, Juliana (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
This research was conducted to find out the perceptions of tutors' teachers towards Culinary School students at FPP UNP in the implementation of learning at SMK Negeri 9 Padang for the January-June 2021/2022 period. This research method is a quantitative descriptive approach. The population of this study were all culinary teachers who became tutors in the January-June 2021/2022 period, namely 10 people. Sampling was carried out using the total sampling technique. Data was collected through a questionnaire using a Likert scale. The results of this study indicate that the perception of tutor teachers towards PLK students in the implementation of learning is good with a percentage of 73%. For preliminary learning activities, the degree of achievement of perception is 71% in the good category; for the core learning activities of 73.5% in the good category; for closing learning activities it 74.4% in the good category.